EMPLOYEE PERFORMANCE ASSESSED FROM COMMITMENT, MOTIVATION, WORK EXPENSE, AND WORK DISCIPLINE STUDY AT THE RAILWAY NURSERY CENTER OF DIRECTORATE GENERAL OF RAILWAY, MINISTRY OF TRANSPORT - Adi Putro, Soesianto Wibowo; Istiatin, Istiatin; Mursito, Bambang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to determine whether there is a significant influence between the variables of commitment, motivation, workload, and work discipline on employee performance. In addition, it is also to determine whether there is a significant simultaneous influence and which variable is the most dominant in influencing employee performance of the Railroad Maintenance Center employees of the Directorate General of Railways of the Ministry of Transportation. The method used is descriptive quantitative method. The population in this study amounted to 81 employees and the entire population was sampled in this study, where the sampling technique used quota sampling. The data used are primary data and secondary data with data collection techniques: observation, documentation, questionnaire and literature study. The data analysis technique in this study used multiple linear tests. The results of the study can be concluded that: The results of the study can be concluded that: 1) There is an effect of commitment, motivation, workload, and work discipline that have a simultaneous and significant effect on employee performance of the Railroad Maintenance Center employees., 2) There is an effect of commitment, which has a positive and significant effect on Employee performance at the Railway Maintenance Center employees, 3) There is an influence of motivation has a positive and significant effect on employee performance on the employees of the Railway Maintenance Center, 4) There is an effect of workload has a positive and significant effect on employee performance on the employees of the Railway Maintenance Center, 5) There is an influence of Discipline work has a positive and significant effect on employee performance at the Railway Maintenance Center employees. Keywords: Employee Performance, Commitment, Motivation, Workload, Work Discipline